Implementasi Inovasi e-Kelurahan dalam Meningkatkan Pelayanan Publik di Kota Padang - Dwi Rizka Witria Gewe; Aldri Frinaldi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The city of Padang as a Smart City city released an innovation program with the use of technology, namely e-Kelurahan. E-Kelurahan is a service innovation that aims to make it easier for the community to take care of letters according to their needs in the Kelurahan can be done manually by the Kelurahan operator or by the community itself. Merode The research used in writing this article is a qualitative research method. This article uses descriptive method research with deductive implication. The data collected is data derived from interview manuscripts, field notes, personal documents, memo notes and other official documents. The sample of villages selected in writing this article is the New Flamboyant Village, Padang Barat District, Padang City, the theory used in testing the implementation of e-Keluraham innovation, according to George C. Edward III. Based on the results of the study, it shows that the implementation of e-kelurahan innovation in improving public services in the city of Padang has been well implemented by village operators but not by the community as a whole. The obstacles found in implementing this e-kelurahan are internal to the organization and external to the organization. The efforts made in facing the obstacles that occur are by continuing to carry out socialization to the community about the benefits of using the e-kelurahan application and conducting training and improvements to this e-kelurahan application to make it simpler and more efficient so that people can easily use this application so that in the end public services to the community can improve.